Cyberbullying sebagai Kekerasan Berbasis Gender Online: Dampak terhadap Remaja serta Peran Keluarga - Aprilia Anggi Permatasari (Pusat Studi Wanita dan Keluarga UGM, 2022)
Cyberbullying is one of the violent phenomena that we still encounter today. Cyberbullying is violent behavior that is carried out intentionally by a strong individual or group to continuously oppress or hurt weak individuals or groups by means of information technology communication, such as social media. This study was used to determine the impact of the cyberbullying phenomenon, especially on adolescents and to determine the role of the family in responding to this phenomenon. This research is a library research using a qualitative descriptive method. The data collection technique is in the form of documentation from secondary data sourced from research studies journals, news, survey institute data and government regulations. The results showed that cyberbullying can have a very serious impact on victims, both psychologically, physically, and socially. More severe cyberbullying tends to increase suicidal ideation. In addition to having an impact on victims, cyberbullying can also have an impact on perpetrators. The role of families, especially parents, is very important in responding to the phenomenon of cyberbullying, both as an effort to prevent and handle it.